The book : a blessing for the soul; the book : recollection and admonishment - Švent, Rozina (Two Homelands, 2001)
The content of the treatise enlightens two fundamental views on publishing books in the emigrant environment. On the one hand that is a unique literary pleasure for the both, the author (declaration) and the reader; on the other hand, beside literature books other are being published in emigration, which have above all an informational-documentation intention. That fact is even more important with themes that enlighten the events during the War (1941-1945), as the Slovene after-War history was dealt in black and white; some themes were “tabooed” (for example the returning and the killing of domobranci (members of home guards) and as such not dealt with until the middle of the seventies.